TO THE RECOMMENDATION OF USING “LINGUISTIC FINGERPRINTS” IN THE CRIMINAL PROCEDURE - ELEK, Balázs (Comparative Legilinguistics, 2016)
The author is a High Court judge of Criminal Division, and university lecturer. He wrote his PhD dissertation “Influencing testimonies in the criminal procedure” in 2008. His field of research includes the common area of forensics and applied linguistics, forensic linguistics. In his present research, he is discussing the questions of using linguistic evidence in forensics and criminal procedures, primarily from the perspective of identification and verification theory. It occurs more and more often that a forensic linguist is hired during the criminal procedure, who assists in drawing conclusions about the authors and the making of different texts by analyzing them. A forensic linguistics expert may also provide a lot of information on the linguistic data coming from what was heard during the confessions (effects of word usage, sentence structure, wording, stereotypes). This is important when searching for the truth in criminal cases because often the meaning of linguistic communication is not found in the particular words. Thus the judge is expected during making a decision to be familiar with the accomplishments of forensic linguistics, and of other related sciences, such as sociology, sociolinguistics, and psychology. The research method is the study of forensic files. The aim of his research is to lower the rate of false judicial decisions, and to increase the extent to which judges' decisions cover reality.